Upaya Guru dalam Mengatasi Kesulitan Perkalian pada Siswa Diskalkulia di Kelas III MI Nurul Falah 3 - Irma Agustin; Retno Andriyani; Serawati Serawati; Elsa Rizqina Agustin; Rizkia Putri Awalina (Lembaga Pengembangan Kinerja Dosen, 2026)
Dyscalculia is a difficulty in learning mathematics that is commonly experienced by elementary school students, especially in multiplication materials. Students with dyscalculia experience obstacles in understanding the concept of numbers and calculation operations, which has an impact on low learning outcomes and students' confidence in mathematics learning. This study aims to describe the difficulties of learning multiplication in dyscalculia students in grade III of MI Nurul Falah 3, as well as identify learning efforts that can help overcome these difficulties. This study used a qualitative approach with a case study design on two students who were identified as having dyscalculia. Data collection techniques include observation, diagnostic assessment, interviews with students and teachers, and analysis of learning outcomes. The results showed that students had difficulty recognizing number symbols, often flipped numbers, and were not able to complete simple multiplication independently. Concrete learning using the